ANALISIS KEBUTUHAN MODEL PEMBELAJARAN KOLABORATIF BERBASIS MINDFULNESS UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA SMP DI PEMALANG - Dewi, Amalia Sari; Basukiyatno, Basukiyatno; Nafiati, Dewi Amaliah (Jurnal Dedikasi Pendidikan, 2025)
This article discusses the need for a collaborative learning model based on mindfulness to improve the social skills of junior high school students in Pemalang Regency. The study aims to evaluate the expectations and needs of students and teachers regarding a learning approach that integrates collaboration and mindfulness practices into the learning process. This research employed a Research and Development (R&D) method, involving 30 students and 6 teachers as the sample, selected through purposive sampling. Data were collected using questionnaires, in-depth interviews, and classroom observations of collaborative learning activities. The data were analyzed using thematic qualitative analysis for interview and observation results, and descriptive quantitative analysis for questionnaire data. The findings indicate a strong interest in a learning model that not only promotes teamwork but also helps students become more aware of themselves and their social environment. These results confirm that a collaborative learning model integrated with mindfulness can effectively enhance students' social abilities, such as communication, empathy, cooperation, and conflict management.